Redescriptions and lectotype designations for two neotropical Elminae (Coleoptera: Elmidae) - Monte, Cinzia; Mascagni, Alessandro (Zootaxa, 2016)
Two Elminae, Macrelmis germaini (Grouvelle, 1896) and Cylloepus reitteri Grouvelle, 1889 from Grouvelle’s Collection in the Museum National d’Histoire Naturelle, Paris are reviewed, and their lectotypes designated. Habitus photographs and illustrations of aedeagi for both species are also included.